Pemanfaatan Pojok Baca Dalam Meningkatkan Minat Baca Siswa di SD Negeri 1 Baubau - Azaz Akbar; Suarti Suarti; Manan Manan; Nasrullah Nasrullah (Journal on Education, 2025)
This research aims to examine the use of reading corners in increasing students' reading interest in elementary schools. This type of research is descriptive qualitative which aims to reveal the context of the use of reading corners in fostering students' interest in reading at SD Negeri 1 Baubau. The results of this research show that the availability of a reading corner at SD Negeri 1 Baubau based on the research results shows that it has been implemented well, although there are still shortcomings such as data collection on reading books that have been read by students has not been carried out and the design of the reading corner has not been implemented in classes III and IV. . The Teacher's Role in Implementing and Utilizing Reading Corners. Based on the theory used and field conditions, both from observations and interviews with the homeroom teacher, the teacher has carried out his main duties well, but is hampered by a community environment that has minimal awareness of reading.